Atypical X-Chromosome Inactivation in an X;1 Translocation Patient Demonstrating Xq28 Functional Disomy - Cottrell, Catherine E (2009)
X-chromosome inactivation is an epigenetic process used to regulate gene dosage in mammalian females by silencing genes on one X-chromosome. While the pattern of X-chromosome inactivation is typically random in normal females, abnormalities of the X-chromosome may result in skewing due to disadvantaged cell growth. We describe a female patient with an X;1 translocation [46,X,t(X;1)(q28;q21)] and unusual pattern of X-chromosome inactivation who demonstrates functional disomy of the Xq28 region distal to the translocation breakpoint. There was complete skewing of X-chromosome inactivation in the patient, along with the atypical findings of an active normal X chromosome and an inactive derivative X. Characterization of the translocation revealed that the patient’s Xq28 breakpoint interrupts the DKC1 gene. Molecular analysis of the breakpoint region revealed functional disomy of Xq28 genes distal to DKC1. We propose that atypical X-chromosome inactivation occurred in the patient due to a post-inactivation cell selection mechanism likely initiated by disruption of DKC1. As a result, the pattern of X-chromosome inactivation is opposite that of the expected for an X;autosome translocation. Therefore, we suggest the phenotypic abnormalities found in the patient are a result of functional disomy in the Xq28 region.